National and International Poetry and Contemporary Naat - Dr. Aasma Rani; Dr. Aqsa Naseem Sindhu (Zaban-o-Adab, 2024)
Contemporary Naat Poetry, A Style Deeply Rooted in Islamic Tradition, Maintains to Conform and Thrive Each Nationally and Internationally, Charming Audiences with Its Religious Resonance and Poetic Splendor. Naat Poetry, Which Celebrates the Life, Teachings, And Virtues of The Islamic Prophet Muhammad SAWW, Serves as A Profound Expression of Devotion and Reverence Amongst Muslim Groups Worldwide. The Pakistani Poet Amjad Islam Amjad Has Left a Lasting Impression on The World of Urdu Literature Through His Mesmerizing Naat Poetry. Amjad’s Naat Poetry, Which Is Imbued with A Deep Sense of Spirituality and Devotion to The Prophet Muhammad, Resonates Deeply with Audiences All Over the World, Regardless of Their Cultural and Linguistic Backgrounds. Another Prominent Figure in The History of Naat Poetry Is Dr. Aslam Ansari. His Naat Poetry Reflects a Deep Sense of Islamic Tradition and Deep Devotion to The Prophet. Dr. Ansari Is Well-Known Among Naat Poetry Aficionados for His Mastery of Language and Poetry. His Compositions Are Imbued with A Rare Elegance That Captivates Listeners with Their Lyricism and Profound Spiritual Meaning Other Prominent Poets Who Have Contributed to Naat Poetry Include Zahoor Nazar Haider Qureshi, Azhar Adeb, Syed Masood Hassan, Iftikhar Arif, And Others. Their Naat Poetry Resonates with Themes of Love, Devotion, And the Noble Qualities of The Prophet. These Poets Work Together to Create a Collection of Contemporary Naat Poetry, Each Contributing to Its Freshness and Importance in The Twenty-First Century. With Their Captivating Verses and Steadfast Belief, They Honor the Life and Teachings of The Prophet Muhammad Through the Power of Poetry.